INTRODUCING CULTURE THROUGH ENGLISH LOANWORDS FROM BAHASA INDONESIA - Septianasari, Lina (Lire Journal (Journal of Linguistics and Literature), 2023)
Contact among languages enables speakers to borrow particular words from one language to another language. This kind of loanword occasionally brings the cultural values of the borrowed language. Related to this phenomenon, this research aims (1) to describe the phonological change of English loanwords from Bahasa Indonesia, and (2) to describe the cultural elements brought by English loanwords from Bahasa Indonesia. The data for this research was obtained from a book entitled Indonesian Phrasebook, written by Wagner (2006). The Oxford Advanced Learners’ Dictionary (OALD) was used to examine the accuracy of the data. The results show that phonological change occurred in some lexical units as an effect of phonological adaptation of the language, such as lenition, apocope, syncope, sound addition, and vowel breaking. The nativization of Bahasa Indonesia happened in vowels and consonants due to phonological adaptation. Furthermore, the loanwords of Bahasa Indonesia also function as a medium of culture to globally introduce Indonesian culture.